Ensaios sobre preços agropecuários, dinâmica macroeconômica e núcleo de inflação no Brasil. - Oliveira, Lúcia Andrea Sindeaux (2022)
In the trajectory of the Brazilian economy, the agricultural sector stands out as the main driver of the country's economic and social development, due to its ability to generate employment and income. Additionally, a characteristic of the agricultural sector is its cyclical nature and peculiar production circumstances, directly reflecting on the high volatility in agricultural prices. This volatile knowledge gives an idea of the behavior of agricultural prices, and their ability to affect the general price index, which interferes in the conduct of the inflation targeting regime. Given this context, three essays were elaborated. The first analyzes the asymmetries of cycles of agricultural prices, market prices and monetary policy using the time-frequency analysis entitled Wavelet Transform, following Yogo (2008), which allowed the construction of series cycles by analyzing duration, volatility and synchronization. Then, the Harding-Pagan (2002) method was applied to identify economic cycles. Finally, to assess the degree of persistence of these cycles, a VAR model was used, which identified the behavior related to the shocks of the variables. The main results show that, for the IPA-OG-DI, there is a strong volatility both in the growth and recession cycles, when compared with the IGP-M, while in the analysis of the causal relationship of the variations of the M2 and IGP- M, it was verified that the M2 directly affects the IGP-M, presenting a feedback structure between the expansion of M2 and the IGP-M. The second essay analyzes the links between agricultural prices and Brazilian macroeconomic variables, using a Factor Augmented Vector Autoregressive (Favar) model, proposed by Bernanke et al., (2005). The results indicate the existence of common factors between the time series of a set of agricultural goods, where the common fluctuations are especially driven by temporary crop commodities and by livestock products. It is conjectured that the growth of Chinese exports for the cultivation of grains and beef largely explains this empirical regularity. The impulse-response analysis showed that shocks to the common factors of agricultural goods affect the effective exchange rate, also resulting in inflationary pressures. In the third essay, a core measure of inflation for the IPCA with forwardlooking characteristics is developed, that is, a core measure of the IPCA with adequate predictive capacity for the level of future inflation. For this purpose, the multivariate model of unobserved components is used, following Harvey (1990) and Koopman et al., (2000). Using the GDP, IPCA, SELIC and M1 variables, following the work of Bagliano et al., (2002) and Goldfeld (1990). After constructing the core inflation for the IPCA, the conditions for a core measure according to Marques et al., (2003), along with three other core measures provided by the Central Bank of Brazil. Finally, the accuracy of out-of-sample forecasts for the IPCA is tested, using core measures. The results confirm that the core measure constructed by modeling unobserved components follows the conditions of Marques et al., (2003) and has adequate predictive power.